FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK PEMERINTAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Silvana , Lela Agusthira; Poniman, Poniman (LPPM Universitas Putera Batam, 2022)
This research aims to determine the effect of Operating Income Operating Expenses (BOPO) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) at state banks listed in Bursa Efek Indonesia (BEI) during 2016 -2020. The sampling method is purposive sampling. The data used in this research is secondary data obtained from 7 state banks with financial statements for 2016-2020 which were downloaded form the official website of Bursa Efek Indonesia (BEI) www.idx.co.id. The analitycal method of this research is a quantitative method with descriptive statistical test, classical assumption test, multiple linear regression tests, and hypothesis testing with the SPSS version 25 program. The result of this research indicate that the variable operating expenses partially operating income (T test) has a significant effect on ROA with the number of Sig.0,003 < 0,05 and the number of Tcount 3,231 > Ttable 2,03693 and the Loan to Deposit Ratio (LDR) variable partially (Ttest) has no significant effect on ROA with the amount of Sig.0,099 > 0,05 and the total Tcount is 1,698 < Ttable 2,03693 to the ROA of states banks listed in Bursa Efek Indonesia (BEI) 2016-2020.